El agente de cambio en el desarrollo de las organizaciones - Gairín Sallán, Joaquín; Muñoz Moreno, José Luis (Enseñanza & Teaching: Revista Interuniversitaria de Didáctica, 2009)
RESUMEN: Los directivos desempeñan un papel crucial en el éxito de las reformas e innovaciones cuando actúan como agentes de cambio. La presente aportación caracteriza el agente de cambio, reparando en sus principales cualidades, capacidades y actitudes; también, destaca la importancia de una intervención que prime la visión global y estratégica frente a intervenciones parciales, gestione y lidere a la vez y asuma la necesidad permanente de aprender de la práctica. Las actuaciones de los agentes de cambio no acostumbran a desempeñarse en un escenario de facilidades y, a menudo, se encuentran con determinadas problemáticas y resistencias que dificultan la implantación de las mejoras institucionales pretendidas. En cualquier caso, avanzar en el desarrollo de organizaciones educativas exitosas exige otorgar a los agentes de cambio un cierto liderazgo capaz de contribuir al desarrollo de las mismas. ABSTRACT: Directors play a crucial role in the success of reforms and innovations when they act as agents of change. This contribution characterises agents of change, examining their main qualities, capacities and attitudes; it also highlights the importance of an intervention that rewards a global and strategic vision, as opposed to biased interventions, that manages and leads at the same time and that assumes the permanent need to learn from experience. The actions of agents of change do not tend to take place in easy scenarios, and often encounter certain problems and resistances that make it hard to implant the institutional improvements being sought. In whatever case, advancing the development of successful educational organisations requires granting agents of change a certain leadership that is able to contribute to the development of the same. Finally, the confluence between curricular development, organisational development and professional development in efficiency and improvement processes at education centres reminds us of the importance of leadership in the change being focused, most of all, on academic aspects. The position, activity and effectiveness of academic leaders are, in this respect, substantial.